Uncovering the Link between Students' Attitude toward Reading and their Comprehension Abilities - Oktaviana, Anggi Try; Amrina, Rizqy Dwi (English Education Department at FKIP Nommensen University, 2025)
Reading attitude gives good influence to reading comprehension achievement. It means that, those who have good reading attitude will be also have a good reading comprehension achievement. However, based on the preliminary research, the teacher revealed that students who had basic comprehension showed ability while reading, but some other students felt lazy, even before reading the text. Therefore, This study sought to establish a correlation between students' reading attitudes and reading comprehension achievement at SMA Muhammadiyah 1 Palembang. This research is a correlational study. There were two types of instruments used to collect data. The researcher employed a questionnaire to assess reading attitude, and a multiple-choice reading comprehension test. The research population consisted of 426 students. The researcher then took 105 students as the sample using random sampling technique. By using Pearson Product Moment on SPSS in analyzing the data, the researcher found that the sig. t was 0.114, higher than the significant alpha of 0.05 (sig.t > 0.05). It demonstrates Ho1 is accepted, or that there is a negative significant correlate between the students' reading attitude and reading comprehension. The writer also discovered that reading attitude has little impact on the 1.5% reading comprehension achievement at SMA Muhammadiyah 1 Palembang. The remaining 98.5 percent was influenced by various factors.